A Polar‐Cap Patch Detection Algorithm for the Advanced Modular Incoherent Scatter Radar System. Issue 10 (23rd October 2018) - Perry, G. W.; St.‐Maurice, J.‐P.
Abstract: We introduce an algorithm to detect polar‐cap patches in an Advanced Modular Incoherent Scatter Radar data set, using the Resolute Bay Incoherent Scatter Radar—North. Patches are detected by comparing plasma density ( n e ) measurements along each radar beam to a 30‐min running average of the median n e within the field‐of‐view. The algorithm is tested and shown to be an effective tool for polar‐cap patch studies. It is then used to conduct a survey of patches over Resolute Bay for two separate periods of time centered on March and December of 2010. The survey shows that polar‐cap patches are almost always present in both sunlit and nighttime conditions. However, the population is subdued during the day. The patch densities are found to vary by as much as an order of magnitude throughout the day. Their ion temperature is relatively constant, only varying by 100 K between the sunlit and nighttime conditions. By contrast, their electron temperature is very sensitive to the solar zenith angle and changes dramatically around sunrise. Plain Language Summary: We introduce an algorithm to detect polar‐cap patches in a radar data set. Patches are large‐scale F region plasma density enhancements, positive plasma density perturbations above the background plasma density, and are typically observed at high latitudes. The patches are detected by comparing plasma density measurements at different points within the radar's field‐of‐view to a 30‐min running average of the median plasma density within the field‐of‐view. The algorithm is tested and validated and used to analyze data collected by the Resolute Bay Incoherent Scatter Radar—North over several days in March and December 2010. Our analysis reveals that the density of detected patches varies by as much as an order of magnitude throughout the day, and their electron temperature is very sensitive to whether or not the patch is sunlit and changes dramatically around sunrise. Key Points: A novel algorithm to detect and study polar‐cap patches in RISR data sets is developed and validated Polar‐cap patches surveyed with RISR‐N using the algorithm exhibit an order of magnitude density variations during sunlit conditions T e of patches depends on solar zenith angle, with strong sunrise effect